Down Syndrome Combined with Robertsonian Translocation (13;14) Carrier - Lestari, Esa Loyallita; Utari, Agustini; Winarni, Tri Indah; Hendrianingtyas, Meita (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Down Syndrome (DS) is a genetic disorder in the form of adding chromosome 21 due to abnormal cell division. This condition causes a distinctive physical appearance and intellectual impairment. The prevalence of DS is between 10-11 out of 10,000 live births worldwide. A 2-week-old baby presented with complaints of jaundice with the clinical picture of DS. There was a mild increase in fT4 levels, and TSH levels were still within the reference value range. Karyotype examination showed Robertsonian translocation of chromosomes 13 and 14 and several abnormalities, namely trisomy 21.